Respostas

2014-03-31T21:57:36-03:00
-x²+10x-21=0
 (Δ = b² - 4ac = 10² - 4 . (-1) . (-21) = 100 - 84 =16) 

delta= b^2 - 4 a b 
delta = 100 - 4 . (-1) . (-21) 
delta = 100 - 84 
delta = 16 

x= (-b + ou - raiz de delta) / 2 a 
x= (-10 + ou - 4) / 2. (-1) 

x1=( -10 + 4 ) (-2) = -6/-2 = +3 
x2= (-10 - 4) (-2) = -14/-2= +7
1 5 1
2014-03-31T23:29:49-03:00
- x² + 10x - 21 = 0
a = -1
b = 10
c = -21
          
Δ = b² - 4ac
          Δ = 10² - 4 . (-1) . (-21)
          Δ = 100 - 84
          Δ = 16
                      x = - b ± √Δ
                               2a
                      x = - 10 ± √16
                              2 . (-1)
                      x' = -10 - 4 = -14 = 7          
                                -2        -2
                      x'' = - 10 + 4 = -6 = 3      
                                 -2        -2

Espero ter ajudado. Valeu!
2 5 2